Comparative mineralogical and fluid inclusion study of the Hnúst'a-Mútnik talc-magnesite and Miková-Jedl'ovec magnesite deposit (Western Carpathians, Slovakia) - KODERA, PETER; RADVANEC, MARTIN (Boletim Paranaense de Geociências, 2002)
Two type localities, located in two different geological and metamorphic units, have been studied. The Hnúst'a-Mútnik deposit is located in amphibolite facies rock sequences of the Veporic unit, while the Miková-Jedl'ovec deposit (a part of the Dúbrava massive) is located in greenschists facies sequences of the Gemeric unit. On both localities successive crystallisation occurred during three stages of replacement. The first two belong to an older metamorphic process M1, the third corresponds to a younger M2 metamorphic process. During the first stage dolomite1 and calcite1 has formed on the expense of protolithic limestone. The second (major) stage is characterized by crystallization of magnesite. The third stage is represented by dolomite2, talc, chlorite, pyrite. At Hnúst'a-Mútnik this stage is much better developed and is further accompanied by tremolite, phlogopite, clinozoisite, zoisite. Based on the carbonate geothermometry at Hnúst'a-Mútnik the first stage occurred at 280-400°C and the third stage at 490-540°C; at Miková-Jedl'ovec the first stage crystallized at 370-420°C. Fluid inclusion study in magnesite showed the presence of primary brine inclusions, with high concentrations of salts other than NaCl, probably highly evolved evaporated marine waters. Brines from Miková-Jedl'ovec are slightly less saline (23-24 wt% NaCl eq.) and homogenised at lower temperatures (195-248°C) than the brines from Hnúst'a-Mútnik (29-32 wt% NaCl eq., 299- 348°C). Brines are accompanied by CO 2 -rich inclusions with nearly identical parameters at both deposits (1-8 wt% NaCl eq., CO 2 density 0.53 to 0.69 g.cm -3 , Th 307 to 336°C). CO 2 fluids probably result from dissolution of carbonates and are coeval or younger than brines. At Miková-Jedl'ovec also low salinity aqueous fluid inclusions have been identified (3-8 wt% NaCl eq., Th 132-249°C), corresponding to the stage 3. Microthermometric data have been also used to determine pressure and temperature limits related to the second and partially to the third stage of replacement.